Visible light-activated biocompatible photo-CORM for CO-release with colorimetric and fluorometric dual turn-on response - Liu, Jingjing; Hoffmann, Patrick; Steinmetzer, Johannes; Askes, Sven H. C.; Kupfer, Stephan; Goerls, Helmar; Gräfe, Stefanie; Neugebauer, Ute; Gandra, Upendar Reddy; Schiller, Alexander (Polyhedron, 2019)
We introduce a colorimetric as well as fluorometric dual response CO-releasing molecule as Mn(I) tricarbonyl complex with a nitrobenzoxadiazole (NBD) fluorophore. DFT and TD-DFT studies corroborate that extended conjugation in the principal ligand frame will help to release CO at low energy radiation. A very low toxicity of NBD-CORM was observed against LX-2 and HepaRG® human cell lines.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Colorimetric and Fluorometric response; Photo-CORM; TD-DFT calculations; Visible light activation